Implementation of Technology-Based Cooperative Information Systems: Reflections on the International PKM Visit - Hasnita, Evi; Cici Aprilliani; Efriza; Neila Sulung; Zuranda; Yelmi Reni Putri; Ratna Dewi (Journal of Community Service and Application of Science, 2025)
An international Community Service (PKM) activity provides strategic insights into the development of a digital technology-based cooperative information system. This study reflects the results of an academic visit to Malaysian national cooperatives, specifically ANGKASA, which has successfully implemented a technology-based integrated cooperative information system. This reflection identified best practices in member management, transaction recording, and digital financial reporting. The findings indicate that cooperative digitalization not only improves management efficiency and organizational transparency but also strengthens cooperative competitiveness at the national and regional levels. This PKM activity strengthens collaboration between universities and the cooperative movement in supporting the digital transformation of Indonesian cooperatives. The implications of this visit are expected to serve as a reference for the development of cooperative information systems in the academic environment and the wider community.